Reallocation of the use of chemical fertilizers and pesticides to increase the income of vegetable farmers and prevent land degradation - Pudjiastuti, Agnes Quartina; Kaluge, David; Widowati, Widowati (Brawijaya University, 2023)
The study, which aimed to analyze the use of chemical fertilizers and pesticides using the Cobb-Douglas production function approach and their reallocation to increase the income of vegetable farmers and prevent land degradation, was conducted in Sumberejo Village, Batu City, Indonesia. Data were collected from 138 pakcoy (Brassica rapa), celery (Apium graveolens), and red chili (Capsicum annuum) farmers through interviews using a questionnaire. The relationship between input and output was analyzed by regression with the Cobb-Douglas production function. Data validity, reliability, and classical assumption tests were performed to ensure the goodness of fit regression model. Furthermore, the F test and t-test were applied to analyze production response to chemical fertilizers and pesticides. This study revealed that the modeled regression equation is appropriate, where R2 = 0.827-0.933. Vegetable production gives a different response to the use of chemical fertilizers (TSP, Urea, and NPK) and pesticides. Increasing this chemical in pakcoy and celery farming is possible, but it needs to be considered because it has no significant effect on increasing production. The productivity of these two types of plants is relatively high. Farmers need to compare the costs of adding these inputs to additional income and the possibility of land degradation. Chemical fertilizers and pesticides have been excessive in red chili farming, so productivity is very low. There are indications that the land has been degraded, but to be sure, a study is needed on the chemical content of the vegetable fields in Sumberejo Village and the optimal use of chemical fertilizers and pesticides.